Offred's Thymotic Resistance in Margaret Atwood's The Handmaid's Tale. - ZARGARZADEH, HALEH; AVESTAN, SAMRAND (Atlantis (0210-6124), 2025)
Drawing on Francis Fukuyama's notion of thymos or the "desire for recognition," this article aims to examine Offred's resistance in Margaret Atwood's The Handmaid's Tale (1985). Women categorised as the Handmaids live under the strict surveillance of the state of Gilead; deprived of their human rights, the state only values their body's fertile organs. The Handmaids' resistance to this demeaning reduction, particularly Offred's, has been mainly examined from feminist, dystopian or Foucauldian perspectives but not from Fukuyama's critical perspective. By examining Offred's perceptive insight and courage, this article argues that her strong thymotic urge is the primary impetus behind her defiance of Gilead. The findings suggest that by dismantling the Gileadean disciplinary codes sexually, emotionally, intellectually and above all aesthetically, Offred qualifies to become recognised as a full human being with diverse capacities. Her thymos gains her due recognition as an author and a historian and due respect for her fellow Handmaids who, despite the panoptic gaze they are subject to, share with each other a legacy of resistance. By deploying Fukuyama's concept of thymos in The Handmaid's Tale, it is hoped that this article will contribute to novel conceptions of the power-resistance dyad in Atwood's oeuvre and in resistance literature more broadly.